High‐temperature tensile cell for in situ real‐time investigation of carbon fibre carbonization and graphitization processes. (17th October 2016) - Behr, Michael; Rix, James; Landes, Brian; Barton, Bryan; Billovits, Gerry; Hukkanen, Eric; Patton, Jasson; Wang, Weijun; Keane, Denis; Weigand, Steven
Abstract : A unique high‐temperature cell combined with in situ wide‐angle X‐ray diffraction was used to follow the formation of graphitic structure in carbon fibre produced from a polyacrylonitrile precursor. Abstract : A new high‐temperature fibre tensile cell is described, developed for use at the Advanced Photon Source at Argonne National Laboratory to enable the investigation of the carbonization and graphitization processes during carbon fibre production. This cell is used to heat precursor fibre bundles to temperatures up to ∼2300°C in a controlled inert atmosphere, while applying tensile stress to facilitate formation of highly oriented graphitic microstructure; evolution of the microstructure as a function of temperature and time during the carbonization and higher‐temperature graphitization processes can then be monitored by collecting real‐time wide‐angle X‐ray diffraction (WAXD) patterns. As an example, the carbonization and graphitization behaviour of an oxidized polyacrylonitrile fibre was studied up to a temperature of ∼1750°C. Real‐time WAXD revealed the gradual increase in microstructure alignment with the fibre axis with increasing temperature over the temperature range 600–1100°C. Above 1100°C, no further changes in orientation were observed. The overall magnitude of change increased with increasing applied tensile stress during carbonization. As a second example, the high‐temperature graphitizability of PAN‐ and pitch‐derived commercial carbon fibres was studied. Here, the magnitude of graphitic microstructure evolution of the pitch‐derived fibre far exceeded that of the PAN‐derived fibres at temperatures up to ∼2300°C, indicating its facile graphitizability.